Calorimetric evaluation of thermal stability and runaway hazard based on thermokinetic parameters of O, O–dimethyl phosphoramidothioate. (February 2022) - Zhou, Hai-Lin; Jiang, Jun-Cheng; Huang, An-Chi; Tang, Yan; Zhang, Yang; Huang, Chung-Fu; Liu, Shang-Hao; Shu, Chi-Min
Abstract: Accidents related to pesticides have occurred with increasing frequency in recent years. One such accident, involving O, O–dimethyl phosphoramidothioate (DMPAT), which is an essential pesticide intermediate in the manufacture of organophosphorus pesticides, occurred in Taichung, Taiwan, in 2016. The results of thermogravimetric analyzer, differential scanning calorimetry, and vent sizing package 2 experiments revealed that the atmosphere, heating rate, and stirring conditions of DMPAT affect its thermal stability. Multiple thermokinetic methods were adopted to determine the values of thermal safety parameters. Through multiple linear regression, a reaction model of DMPAT was developed. The time to conversion limit and self-accelerating decomposition temperature were determined. The results of this study provide a reference for ensureing the thermal safety of DMPAT processing, use, storage, and transport and preventing thermal decomposition accidents. Highlights: Thermal hazard of O, O–dimethyl phosphoramidothionate (DMPAT) was evaluated. Five kinetic models, including Vyazovkin model, were used for thermokinetic analysis. Safety and thermokinetic parameters were obtained based on different experimental data and various kinetic models. Multiple linear regression was adopted to determine the thermal decomposition reaction model of DMPAT. The TCL and SADT values of DMPAT were determined.